Quantifying Pharmaceutical Film Coating with Optical Coherence Tomography and Terahertz Pulsed Imaging: An Evaluation. Issue 10 (17th June 2015) - Lin, Hungyen; Dong, Yue; Shen, Yaochun; Zeitler, J. Axel
<x xml:space="preserve">Abstract</x> Spectral domain optical coherence tomography (OCT) has recently attracted a lot of interest in the pharmaceutical industry as a fast and non‐destructive modality for quantification of thin film coatings that cannot easily be resolved with other techniques. Because of the relative infancy of this technique, much of the research to date has focused on developing the in‐line measurement technique for assessing film coating thickness. To better assess OCT for pharmaceutical coating quantification, this paper evaluates tablets with a range of film coating thickness measured using OCT and terahertz pulsed imaging (TPI) in an off‐line setting. In order to facilitate automated coating quantification for film coating thickness in the range of 30–200 μm, an algorithm that uses wavelet denoising and a tailored peak finding method is proposed to analyse each of the acquired A‐scan. Results obtained from running the algorithm reveal an increasing disparity between the TPI and OCT measured intra‐tablet variability when film coating thickness exceeds 100 μm. The finding further confirms that OCT is a suitable modality for characterising pharmaceutical dosage forms with thin film coatings, whereas TPI is well suited for thick coatings. © 2015 The Authors. Journal of Pharmaceutical Sciences published by Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:3377–3385, 2015